Intra-articular collagenase injection increases range of motion in a rat knee flexion contracture model - Wong K; Trudel G; Laneuville O (Dove Medical Press, 2017)
Kayleigh Wong,1 Guy Trudel,2 Odette Laneuville3 1Bone and Joint Research Laboratory, The Ottawa Hospital Rehabilitation Centre, Ottawa, Ontario, 2Department of Medicine, Bone and Joint Research Laboratory, The Ottawa Hospital Rehabilitation Centre, Ottawa, Ontario, 3Department of Biology, Faculty of Science, University of Ottawa, Ottawa, Ontario, Canada Objectives: A knee joint contracture, a loss in passive range of motion (ROM), can be caused by prolonged immobility. In a rat knee immobilization flexion contracture model, the posterior capsule was shown to contribute to an irreversible limitation in ROM, and collagen pathways were identified as differentially expressed over the development of a contracture. Collagenases purified from Clostridium histolyticum are currently prescribed to treat Dupuytren’s and Peyronie’s contractures due to their ability to degrade collagen. The potential application of collagenases to target collagen in the posterior capsule was tested in this model. Materials and methods: Rats had one hind leg immobilized, developing a knee flexion contracture. After 4 weeks, the immobilization device was removed, and the rats received one 50 µL intra-articular injection of 0.6 mg/mL purified collagenase. Control rats were injected with only the buffer. After 2 weeks of spontaneous remobilization following the injections, ROM was measured with a rat knee arthrometer, and histological sections were immunostained with antibodies against rat collagen types I and III. Results/conclusion: Compared with buffer-injected control knees, collagenase-treated knees showed increased ROM in extension by 8.0°±3.8° (p-value <0.05). Immunohistochemical analysis revealed an increase in collagen type III staining (p<0.01) in the posterior capsule of collagenase-treated knees indicating an effect on the extracellular matrix due to the collagenase. Collagen I staining was unchanged (p>0.05). The current study provides experimental evidence for the pharmacological treatment of knee flexion contractures with intra-articular collagenase injection, improving the knee ROM. Keywords: joint, contracture, collagen, immobilization range of motion